Peningkatan Minat Budidaya Anggur Generasi Z melalui Experiential Learning Berbasis Komunitas - Dian Diani Tanjung; Dessy Iriani Putri; Sukrianto; Danindra Ziva; Muhamad Zidni Agastia; Candra Kirana Mahameru (FKIP Universitas Mataram, 2026)
Grape cultivation training and workshops were conducted as part of the implementation of the campus impact program to increase student competency and interest in the agricultural sector, particularly grape cultivation in urban and suburban areas. This activity was a collaboration between the Faculty of Agriculture, Muhammadiyah University of Jakarta and the Indonesian Grape Activists Association, involving students from the Agribusiness Study Program as participants. Methods included material delivery, discussions, field practice, and evaluation using pre-tests and post-tests. Materials provided covered prospects for grape development in Indonesia, seedling propagation techniques through grafting, making planting media, introducing superior varieties, and plant pruning techniques. Effectiveness of training was analyzed using a paired sample t-test to measure changes in participants' level of understanding and interest before and after training. Results showed an increase in participants' knowledge and skills related to grape cultivation techniques. In addition, results of the paired sample t-test showed a significant increase in interest after training (t = -4.885; p < 0.001). Enthusiasm of participants contributed to program's success in increasing understanding and interest in grape cultivation. Thus, training has proven effective in increasing student capacity and encouraging growing interest of younger generation to be involved in development of horticultural agriculture.